The Effectiveness of Storytelling On Improving Learning Outcomes of Primary School Students - Nurmalina; Aprinawati, Iis (Universitas Islam Negeri Raden Intan Lampung, 2025)
The widespread use of digital technology has influenced children’s learning focus, often reducing their academic engagement. Alternative pedagogical strategies are therefore needed to strengthen primary students’ learning outcomes. This study aims to analyze the effectiveness of storytelling in improving primary school students’ learning outcomes. A quantitative quasi-experimental design with a non-equivalent control group was employed, involving 76 fourth-grade students divided into experimental and control classes. Data were collected through pre-test and post-test instruments, classroom observation, and documentation, and analyzed using normality tests, homogeneity tests, ANOVA, and independent t-tests. The findings show that the storytelling group achieved significantly higher post-test scores than the control group, with an N-Gain of 0.52 (moderate category) compared to 0.17 (low category). Statistical analysis confirmed the effectiveness of storytelling (p < 0.05) in enhancing students’ conceptual understanding and learning engagement. In conclusion, storytelling is an effective and adaptable strategy for improving primary school students’ learning outcomes and can be integrated as a humanistic and culturally relevant approach in the classroom.